Institutional governance and its relationship to the transparency of educational decisions among school principals of the Directorate of Education, Ramtha District - المقبل براءة; محمد الحراحشة; محمد منيزل عليمات (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The degree of opplication of institutional governance and its relationship to the Ttransparency of School Managers’ Decisions among school principals of the Directorate of Education of the Ramtha Brigade. To achieve the objective of the study, the descriptive correlational survey was used, and a simple random sample was selected consisting of (325) teachers a questionnaire consisted of two axes, the first to measure the degree of institutional governance and included three areas: (transparency, participation, accountability), and the number of its paragraphs reached (16) paragraphs, The second axis is measuring the degree of transparency of educational decisions and included four areas (decisions, laws and legislation, administrative communication, administrative accountability) and the number of paragraphs reached (26) paragraphs, after verifying their validity and stability. The study found that the degree to which Ramtha District school principals practice institutional governance from the teachers’ point of view is high in all areas. The results of the study found that there were no statistically significant differences due to the gender variable in the degree of practice of the principals of Ramtha Brigade schools for institutional governance from the teachers’ point of view, and the results showed that there were no differences due to years of experience for all fields, and the results showed that there were statistically significant differences due to the impact of the variables of scientific qualification and were in favor of the academic qualification bachelor’s degree and less. The results of the study showed that the level of transparency of educational decisions among school principals of the Directorate of Education in Ramtha District from the point of view of teachers was high in all fields, and the results of the study indicated that there were no statistically significant differences in the level of transparency of educational decisions due to the impact of the gender variable in all fields and the total degree, and the results of the study showed that there were differences due to the impact of the scientific qualification in all fields and the total degree and were in favor of the scientific qualification (bachelor’s degree and less), While the results of the study showed that there were no statistically significant differences due to the variable of years of experience. The results of the study found a positive correlation between the areas of institutional governance and the areas of transparency of educational decisions, and in light of the results of the study, the study recommends a set of recommendations, the most important of which are: Circulating the results of this study to a number of directorates of the Ministry of Education in other governorates.